2010
DOI: 10.1051/0004-6361/200911834
|View full text |Cite
|
Sign up to set email alerts
|

The energy spectrum of anomalous X-ray pulsars and soft gamma-ray repeaters

Abstract: Context. Anomalous X-ray pulsars (AXPs) and soft gamma-ray repeaters (SGRs) exhibit characteristic X-ray luminosities (both soft and hard) of around 10 35 erg s −1 and characteristic power-law, hard X-ray spectra extending to about 200 keV. Two AXPs also exhibit pulsed radio emission. Aims. Assuming that AXPs and SGRs accrete matter from a fallback disk, we attempt to explain both the soft and the hard X-ray emission as the result of the accretion process. We also attempt to explain their radio emission or the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 63 publications
7
60
0
Order By: Relevance
“…For event B, the most adequate model for describing the burst spectrum was non-thermal: a power law with an index of 0.42. Such non-thermal behavior is also typical for magnetar bursts (van der Horst et al 2012;Lin et al 2013;Şaşmaz Muş et al 2015). Following the burst, we observed the segments Gray and Oscillation, during which clear periodic modulations at 8.7 s could be seen.…”
Section: Discussionmentioning
confidence: 78%
“…For event B, the most adequate model for describing the burst spectrum was non-thermal: a power law with an index of 0.42. Such non-thermal behavior is also typical for magnetar bursts (van der Horst et al 2012;Lin et al 2013;Şaşmaz Muş et al 2015). Following the burst, we observed the segments Gray and Oscillation, during which clear periodic modulations at 8.7 s could be seen.…”
Section: Discussionmentioning
confidence: 78%
“…In the accretion picture presented by Trümper et al (2010Trümper et al ( , 2013, this is a natural consequence of the fact that only about half of the produced hard X-ray luminosity in the radiative shock is observed directly (L h ), while the other half is intercepted by the polar cap and the major fraction of it is reemitted as soft X-rays (L s ). With our reported calculations in Sect.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed model for the formation of the quiescent spectra of AXPs/SGRs has been proposed by Trümper et al (2010Trümper et al ( , 2013 using the fallback disk model. These spectra consist of two components (e.g., den Hartog et al 2008a,b;Enoto et al 2010); a quasi-thermal component at low energies, which is generally attributed to the photospheric emission from the neutron star polar cap, and a hard power-law component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the frame of the disk model, rotational properties and X-ray luminosity of this SGR can be reached simultaneously within the cooling timescale of a neutron star with B 0 10 12 G (Alpar et al 2011). Recently, Trümper et al (2010) showed that the high-energy spectrum of AXP 4U 0142+61 can be produced in the accretion column of this source mainly by the bulk Comptonization process.…”
Section: Introductionmentioning
confidence: 98%